PTH-034 A novel endoscopic technique to manage buried bumper syndrome in peg: the olympus hookknife. (17th June 2017) - Wolpert, L; Summers, D; Tsang, A
Abstract : Introduction: Buried bumper syndrome (BBS) is an uncommon but serious complication of percutaneous endoscopic gastrostomy (PEG) with an incidence of 0.3%–2.4% per PEG patient year. It involves the internal fixation device, or 'bumper', migrating into the gastric wall and subsequent mucosal overgrowth. Symptoms include inability to insert the PEG tube, loss of patency and leakage from the PEG. Method: We described a case series of four patients with BBS treated with a novel endoscopic technique using a HookKnife between June 2016 and February 2017. The HookKnife is a rotating l-shaped cutting wire designed for hooking tissue and pulling it away from the gastric wall towards the lumen. Patients were selected for treatment following referral for suspected BBS which was then evaluated by endoscopy. Results: Two patients had the procedure in endoscopy under sedation and two in theatre under general anaesthetic. The indications for PEG feeding were tetraplegia, cerebral palsy, Huntington's disease and multiple sclerosis. The age range of patients was 28–62 years. In each case the external PEG tubing was cut short approximately 5 cm from the abdominal wall. A 15 mm through the scope (TTS) dilation balloon was passed externally via the PEG tubing and inflated to dilate the mucosal orifice. The orifice was then visualised and the HookKnife was deployed to incise the gastric mucosa over the buried bumper using two to three radial incisions each approximately 5 mm in length. The TTS balloon was inflated inside the tubing at the level of the PEG bumper and the tubing and balloon catheter clamped together using artery forceps. Short but firm controlled pressure was applied towards the gastric lumen to force the bumper into the stomach. The PEG was then removed using a standard snare technique. The HookKnife technique was successful in all four cases with no complications. Each patient was discharged on the day of treatment. Conclusion: The HookKnife is a manoeuvrable, safe and effective device for endoscopic removal of buried PEG bumpers and allows the avoidance of surgery in a high risk group of patients. The benefit of the HookKnife technique compared with techniques that rely on incising the mucosa towards the gastric wall is that the HookKnife allows elevation of the gastric mucosa away from the bumper. This additional level of control allows a more precise incision, more accurate evaluation of the depth of the bumper migration and reduces the risk of inadvertent gastric perforation. To our knowledge this technique has not been described previously and we suggest that this technique should be added to the treatment algorithms for the management of BBS. Reference: . Cyrany J, Rejchrt S, Kopacova M, Bures J. Buried bumper syndrome: A complication of percutaneous endoscopic gastrostomy. World J Gastroenterol. 2016Jan 14; 22(2): 618–627 Disclosure of Interest: None Declared